Managing spot blotch disease in wheat: Conventional to molecular aspects - Roy, Chandan; He, Xinyao; Gahtyari, Navin C.; Mahapatra, Sunita; Singh, Pawan K. (Frontiers in Plant Science, 2023)
Spot blotch (SB) caused by Bipolaris sorokiniana (teleomorph Cochliobolus sativus) is one of the devastating disease of wheat in the warm and humid growing areas around the world. An average yield loss of 15-20% is recorded in the experimental plots and farmers’ fields, which may exceed 50% when susceptible varieties were cultivated under SB disease conducive environments. The fungus is transmitted mostly through infected soil, straw or seeds, and a large number of alternative hosts have been reported in the cultivated and wild plant species. B. sorokiniana can infect leaves, stem, roots, rachis and seeds; it also produces toxins like helminthosporol and sorokinianin. Naturally, the fungus multiples through asexual conidia, but it is genetically variable, highly virulent and aggressive. No wheat genotype has been identified as immune to SB; therefore, integrated disease management strategies should be adopted. Resistance is mostly quantitative, being governed by QTLs with minor to moderate effects. Only four QTLs with major effects have been designated as Sb1 through Sb4, whereas minor QTLs have been mapped on almost all the wheat chromosomes. Fine mapping and cloning of SB resistance QTLs and understanding of the molecular basis for SB resistance will be useful for development of resistant genotypes.